1978
DOI: 10.1116/1.569850
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium selenide thin-film transistors

Abstract: Vacuum-deposited CdSe thin-film transistors (TFT’s) with reproducible good stability, performance, uniformity, and yield were made using sputtered SiO2 gate insulator, Cr source–drain (s–d) electrodes, and postdeposition annealing in N2. These materials and procedures permit the use of multiple pumpdown fabrication methods with no loss in ac characteristics and little sacrifice in dc stability. Promising results were obtained using photolithography (PL) to delineate s–d electrodes, further simplifying fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Furthermore, identification of the appearing crystalline peaks confirmed that both the cubic and the hexagonal phases of CdSe exist in all the deposited films. Peak positions and relative intensities are in very good agreement with the results noted in the JCPDS-IDCC files [19] and previous works [17,20]. Any additional peak which does not belong to one of those phases exists in the diffractograms.…”
Section: Structural Characterizationsupporting
confidence: 89%
“…Furthermore, identification of the appearing crystalline peaks confirmed that both the cubic and the hexagonal phases of CdSe exist in all the deposited films. Peak positions and relative intensities are in very good agreement with the results noted in the JCPDS-IDCC files [19] and previous works [17,20]. Any additional peak which does not belong to one of those phases exists in the diffractograms.…”
Section: Structural Characterizationsupporting
confidence: 89%
“…The nanocrystalline films prepared in this work are comparable to polycrystalline thin films of CdSe formed by evaporation and electrodeposition. 44 , 49 52 These films have electron mobilities ranging from 3 to 100 cm 2 /(Vs) and carrier concentrations ranging from 10 11 to 10 18 cm –3 , which are sensitive to the grain size, annealing temperature, and are enhanced by doping with indium. 47 , 53 , 54 In these studies, the grain size in the high-performance materials approaches 100 nm; however, our work clearly demonstrates that strong electronic coupling between nanocrystalline grains (<5 nm) can reliably produce films with comparably high carrier mobilities (10–20 cm 2 /(Vs)) and low carrier concentrations (10 16 cm –3 ).…”
Section: Resultsmentioning
confidence: 99%
“…These techniques allow, in principle, the growth of high purity homogeneous films with thickness from a few tens of nanometers up to the microme-ters range and with controlled metal atomic fractions in a wide range. Although O 2 is commonly added to Ar to obtain high quality SiO 2 films by rf sputtering of SiO 2 targets, 9 Author to whom correspondence should be addressed; Viale Università, 2-35020 Legnaro (PD), Italy; electronic mail: vomiero@lnl.infn.it addition when Ag and SiO 2 are cosputtered has been reported only for films with thickness in the nanometer range to our knowledge. 5,6 Sputter deposition has also been used.…”
Section: Introductionmentioning
confidence: 99%